ICT w edukacji, profilaktyce i terapii – przykłady dobrych praktyk - Borzucka-Sitkiewicz, Katarzyna; Leksy, Karina (Wydawnictwo Naukowe UAM, 2018)
The dynamically developing global IT infrastructure and the increasing importance of modern information technologies represent a huge challenge in the process of socialization and education of children and young people. Undoubtedly, it is extremely important to prepare current and future generations for a skillful use of modern technologies. Therefore, it is essential to implement new technologies in the teaching process at all levels of education as well as during preventive and therapeutic activities. This study analyzes the functioning of three institutions that use modern information technology within educational, preventive and therapeutic interventions. These institutions have been selected to be environmentally diverse, show the international context and demonstrate a different potential for ICT use. The main objective of the research was to identify innovative ways of using modern technologies in supporting educational and compensatory activities undertaken by selected institutions.
Keywords: modern information technologies; education; prevention; therapy